ANALYSIS OF VRF AC UTILITY SYSTEM IN THE INTEGRATED LECTURE BUILDING OF THE BANYUWANGI STATE POLYTECHNIC (Case Study at Banyuwangi State Polytechnic): ANALISIS SISTEM UTILITAS AC VRF PADA BANGUNAN GEDUNG KULIAH TERPADU POLITEKNIK NEGERI BANYUWANGI (Studi Kasus Pada Politeknik Negeri Banyuwangi) - HARI PRANOTO; Sunarko; Mahfud (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
As time goes by, temperatures in Indonesia have increased quite drastically. According to daily BMKG data, the average temperature in Banyuwangi Regency is between 240C – 330C (BMKG, 2023). Installing an air conditioner (AC) is considered very necessary to obtain a comfortable temperature in the body. There are several methods to get the right AC capacity (PK) according to the size of the room. The data collection method for this research was carried out by measuring and observing each room in the Banyuwangi State Polytechnic Integrated Lecture Building. When measuring, the data taken includes the length and width of the room. Then proceed with observing the type of AC installed in the room and then analyzing it with the technical specifications used. By comparing the name of the plate with the measurement results, it can be seen that all rooms comply with the AC capacity installation standards. In the Poliwangi Integrated Lecture Building, the indoor AC uses a Cassette type AC, where the AC is installed on the ceiling. The AC system used in the GKT Poliwangi building uses a VRF AC system using single channel ducting. The object of measurement includes the length and width of the room and then multiplied by 500 (the value of 500 is obtained from the average height of the room not exceeding 5 meters). VRF AC cleaning maintenance efforts are usually carried out every 3-6 months.